(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Noise is a major problem in modern industrial activities. The use of machines in industry and inseparable design of work between humans and machines makes workers exposed to noise as one of the physical hazards in the work environment. Noise can cause physiological reactions such as systolic and diastolic blood pressure disorders. However, systolic blood pressure response is more sensitive to changes. The systolic pressure after loading is normally up (20 mmHg), the rest is considered abnormal and is considered one of the risk factors for cardiovascular disease. Blood pressure is a multifactorial health indicator. In addition to noise, blood pressure is also influenced by the physical workload that workers receive as one of the factors of workload. The purpose of this study is to examine the relationship of noise and physical workload to an increase in systolic blood pressure. This is a cross sectional design and observational analytical study with statistical tests using spearman. Respondents were determined through simple random sampling technique that results in a sample of 36 ceramics industry workers in the production line section. The results showed the value of the noise relationship (r = 0.581) towards the increase in systolic blood pressure. Physical workload showed a relationship value of (r = 0.666) towards the increase in systolic blood pressure. The direction of the relationship between the independent variable and the dependent variable is positive, which means that the higher the noise level and physical workload, the higher the risk of abnormal systolic blood pressure.